THE PRIME COST OF FREIGHT TRANSPORT IN THE FORMATION OF TARIFFS IN THE INTERNATIONAL TRAFFIC - Shevchenko, I. V. (Science and Transport Progress, 2009)
The article is dedicated to the problem concerning a transport barrier in international transportation, a transport process effectiveness and expedition goods between Ukraine and others countries. This article sets up and explores such question as transport corridor and its meaning.